2020
DOI: 10.1111/joim.13096
|View full text |Cite
|
Sign up to set email alerts
|

Male reproductive health and intergenerational metabolic responses from a small RNA perspective

Abstract: The world has recently experienced a decline in male reproductive (e.g. sperm counts and motility) and metabolic (e.g. obesity and diabetes) health. Accumulated evidence from animal models also shows that the metabolic health of the father may influence the metabolic health in his offspring. Vectors for such paternal intergenerational metabolic responses (IGMRs) involve small noncoding RNAs (sncRNAs) that often increase in spermatozoa during the last days of maturation in the epididymis. We and others have sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 164 publications
(217 reference statements)
2
29
0
Order By: Relevance
“…Like rRFs, tRNA derived sRNA (tRFs) can also originate from the 5’ or 3’ terminal. In addition, internal (i’) fragments, which neither start nor end in the terminals of full-length tRNA have been described [26, 27]. We used these classifications as an independent confirmation of the differences in 5’ and 3’ affinities between the 5P- and 5X-type libraries that we observed in sRNA derived from rRNA.…”
Section: Resultsmentioning
confidence: 99%
“…Like rRFs, tRNA derived sRNA (tRFs) can also originate from the 5’ or 3’ terminal. In addition, internal (i’) fragments, which neither start nor end in the terminals of full-length tRNA have been described [26, 27]. We used these classifications as an independent confirmation of the differences in 5’ and 3’ affinities between the 5P- and 5X-type libraries that we observed in sRNA derived from rRNA.…”
Section: Resultsmentioning
confidence: 99%
“…The impact of nutrients or other environmental insults on the function of the tRNA-modifying enzymes TRMT10A or CDK5RAP1 remains to be investigated [73,97]. The deleterious effect of 5 -tRNA Gln fragments generated in TRMT10A-deficient pancreatic β-cells [53], as well as the high fat feeding-induced tRHs that contribute to the nongenetic inheritance of metabolic traits [30,55,213,215] highlight the importance of tRNA fragmentation on cell functionality. The molecular mechanisms associating these tRNA fragments with insulin resistance and β-cell dysfunction are still largely unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Intergenerational inheritance in humans is difficult to study experimentally. There is increasing evidence, however, that diet affects both male fertility and offspring predisposition to metabolic diseases (reviewed and summarized in Natt et al [213]). RNA sequencing showed that tRHs are the most frequent type of small RNA in human sperm [206,214].…”
Section: Trna Fragments In Intergenerational Inheritance Of Metabolicmentioning
confidence: 99%
“…The role of sncRNA in spermatogenesis was reviewed in a recent paper (Natt, Ost, 2020). Composition of different sncRNAs changes dynamically throughout spermatogenesis cycle (74 days in humans, 56 days in rat (Creasy, 1997)) (Sharma, U. et al, 2016.…”
Section: Sncrna In Spermmentioning
confidence: 99%